2009
DOI: 10.1111/j.1365-2125.2009.03392.x
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of sirolimus in de novo Chinese adult renal transplant patients

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT?• Sirolimus is an immunosuppressive agent used for the prophylaxis of renal allograft rejection.• Several conventional pharmacokinetic and population pharmacokinetic studies have been conducted to assess the pharmacokinetic characteristics of sirolimus in White or African-American recipients. WHAT THIS STUDY ADDS?• The population pharmacokinetics of sirolimus in Chinese adult renal transplant recipients was characterized for the first time.• New drug-drug interactions b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 68 publications
(147 reference statements)
7
44
0
Order By: Relevance
“…Although there were no formal statistical comparisons performed, the observed mean oral clearance of sirolimus in this study for patients receiving CsA appears to be consistent with values reported from studies mainly in white and black patients using NCA (133–143 mL/h/kg) . It is also in agreement with the estimates from Chinese renal transplant patients using a population approach (168 mL/h/kg [10.1 L/h]) for sirolimus. It should be noted that when the relevant mean C trough value in patients taking concomitant CsA was normalized to a 2‐mg dose (7.0 ± 3.6 ng/mL), it appeared to be consistent with the mean trough concentration values (8.59 ± 4.01 and 8.06 ± 4.03 ng/mL) observed in two pivotal phase 3 trials in renal transplant patients, taking into consideration that different bioanalytical methods were employed for quantification of sirolimus .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although there were no formal statistical comparisons performed, the observed mean oral clearance of sirolimus in this study for patients receiving CsA appears to be consistent with values reported from studies mainly in white and black patients using NCA (133–143 mL/h/kg) . It is also in agreement with the estimates from Chinese renal transplant patients using a population approach (168 mL/h/kg [10.1 L/h]) for sirolimus. It should be noted that when the relevant mean C trough value in patients taking concomitant CsA was normalized to a 2‐mg dose (7.0 ± 3.6 ng/mL), it appeared to be consistent with the mean trough concentration values (8.59 ± 4.01 and 8.06 ± 4.03 ng/mL) observed in two pivotal phase 3 trials in renal transplant patients, taking into consideration that different bioanalytical methods were employed for quantification of sirolimus .…”
Section: Discussionsupporting
confidence: 90%
“…Despite differences in the sirolimus dosing regimens, in patient demographic characteristics and disease states, and in the combination therapies between this study and those used in previous investigations, the pharmacokinetic parameters are generally consistent with those reported in studies in Western populations and are consistent with those suggested from a previous population pharmacokinetic analysis in Chinese renal transplant recipients …”
Section: Discussionsupporting
confidence: 87%
“…Sirolimus has low bioavailability (14% on average) and a long terminal elimination half‐life of ~62 h 7 . Studies in transplant patients have demonstrated marked interindividual pharmacokinetic variability, resulting in the widespread use of therapeutic drug monitoring based on whole blood concentrations 8 , 9 , 10 , 11 , 12 , 13 …”
mentioning
confidence: 99%
“…18-21 Differences in apparent oral clearance between our population and others may be related to variability in cyclosporine use and exposure, differences in extent of CYP3A4 and CYP3A5 expression, other disease states (e.g., liver disease and cancer), and other drug interactions. 18,19,22,23 Unlike other studies that have developed population PK models, we identified age as an important covariate for apparent clearance. This finding may reflect the relatively more advanced median age of patients in our study (59, range 29 to 72 compared to 48.6, range 20 to 69), and potential influences of age on CYP3A4 activity.…”
Section: Discussionmentioning
confidence: 99%